2020
DOI: 10.14710/nmjn.v10i3.32457
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Nurses’ Knowledge and Attitudes on Paediatric Pain: A Descriptive Cross-Sectional Survey in a Developing Country

Abstract: Background: Children’s nurses’ knowledge of pain affects their pain management practices. Even though poor knowledge and attitudes have been reported in several studies, most were carried out in developed settings. However, little has been reported on the management of paediatric pain by nurses in resource-limited settings such as in sub-Saharan Africa.Purpose: This study sought to assess the knowledge and perceptions of children’s nurses regarding paediatric pain in a Ghanaian context.Methodology: A descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…The total PNKAS-N mean score at T1 in the present study was lower than a few other PNKAS studies (12, 14, 79, 94, 99), but slightly higher than most previous studies (13, 15, 76, 78, 80, 81, 83-88, 95-98, 148), however, it did not reach an acceptable level of knowledge (84).The present study revealed PACU nurses' knowledge gaps in essential areas, especially regarding pharmacological management. These knowledge gaps concur with the other more recent studies using PNKAS, such as useful drugs for treatment of pain in children (83), risk of addiction (83,(85)(86)(87)96) and respiratory depressions (83,86,96). Healthcare professionals' knowledge is essential in pediatric pain management.…”
Section: Pediatric Postoperative Pain Management In Pacus In Norwaysupporting
confidence: 83%
See 3 more Smart Citations
“…The total PNKAS-N mean score at T1 in the present study was lower than a few other PNKAS studies (12, 14, 79, 94, 99), but slightly higher than most previous studies (13, 15, 76, 78, 80, 81, 83-88, 95-98, 148), however, it did not reach an acceptable level of knowledge (84).The present study revealed PACU nurses' knowledge gaps in essential areas, especially regarding pharmacological management. These knowledge gaps concur with the other more recent studies using PNKAS, such as useful drugs for treatment of pain in children (83), risk of addiction (83,(85)(86)(87)96) and respiratory depressions (83,86,96). Healthcare professionals' knowledge is essential in pediatric pain management.…”
Section: Pediatric Postoperative Pain Management In Pacus In Norwaysupporting
confidence: 83%
“…Results from PNKAS studies of nurses conducted in the Kingdom of Saudi Arabia (83), Ghana (84,85), Turkey (76), Mexico (13,87), Egypt (97), China (88), Mongolia (95) and Iran (98) showed low total mean scores, with < 50% correct answers. Studies conducted in the USA (12, 78-80, 96, 99), Canada (14,15,94), Norway (77), Spain (86) and Germany (81) showed higher total mean scores, with 56-82% correct answers.…”
Section: Nurses' Knowledge and Attitudes Regarding Pediatric Painmentioning
confidence: 98%
See 2 more Smart Citations